AN ANALYSIS OF TEACHERS’ QUESTIONING STRATEGIES DURING INTERACTION IN THE CLASSROOM: A CASE OF THE EIGHT GRADE SMP PGRI 01 SEMARANG - A B Prabowo; Alfiyanti Alfiyanti (ETERNAL (English Teaching Journal), 2013)
The objectives of this study are;1) to know kinds of teachers’ questioning strategies that teacher use in the classroom. 2) to know the way the teachers use the questioning strategies in the classroom. The design of the research is descriptive qualitative. The writer got the data of this research from interview notes. The observation sheet source of the data research were from the teacher and students. The Instrument used are observation sheet, interview, and document. The techniques for analyzing the data is descriptive. The steps were; comprising interactive reducing the data, presenting the data, and drawing conclusion. The result of this research shows that are: 1) The teaching strategies are; (a) the teaching techniques used lecturing, group project and small group discussion, (b) the seating arrangement, the students seating position changed, (c) the teacher give feedback when the students have difficulties, the teacher give some clue to the students to help them understand the material given, (d) the teacher evaluates the students: the teacher given task and motivations for the students. 2) The problems faced by the teacher are the classroom conditions, the crowded conditions, controlling individually, the interaction between the teacher and students in the classroom is ineffective, the students' less vocabulary, the limited media and the problems faced by the students are lack of confidence, the students have difficulties in translation. The conclusion are Not all English teachers in SMP PGRI 01 Semarang have good understanding of how to implement teacher’s questioning. Some of them still have some problems with their understanding. It is caused by some reasons, such as: (1) the teachers do not want to get out of their comfort zone, some of them are thinking that the most important part of teaching is how to make the students understand the materials; (2) they can not move on from their old views of teaching English in the classroom; (3) last but not least, because the training done by the authoritative government is not sufficient to make them mastering teacher’s questioning.